A global approach to long‐term follow‐up of targeted and immune‐based therapy in childhood and adolescence. Issue 7 (16th April 2021) - Kieran, Mark W.; Caron, Hubert; Winther, Jeanette Falck; Henderson, Tara O.; Haupt, Riccardo; Hjorth, Lars; Hudson, Melissa M.; Kremer, Leontien C.M.; van der Pal, Helena J.; Pearson, Andrew D.J.; Pereira, Leonardo; Reaman, Gregory; et al.
Abstract: While considerable efforts and progress in our understanding of the long‐term toxicities of surgery, radiation and chemotherapy in children with cancer have been made over the last 5 decades, there continues to be a wide gap in our knowledge of the long‐term health impact of most novel targeted and immunotherapy agents. To address this gap, ACCELERATE, a multi‐stakeholder collaboration of clinical and translational academics, regulators from the EMA and FDA, patient/family advocates and members spanning small biotechnology through to large pharmaceutical companies have initiated the development of an international long‐term follow‐up data registry to collect this important information prospectively. Providing critical safety data on the long‐term use of these approved and investigational therapies in children will support the regulatory requirements and labeling information. It will also provide the necessary insight to help guide physicians and families on the appropriateness of a targeted or immune therapy for their child and inform survivorship planning.